2012
DOI: 10.1002/lary.23739
|View full text |Cite
|
Sign up to set email alerts
|

The role of high‐dose‐rate and pulsed‐dose‐rate brachytherapy in the management of recurrent or residual stomal tumor after total laryngectomy

Abstract: The results of our study show that HDRBT and PDRBT are feasible in previously irradiated patients with recurrent or residual stomal tumor after total laryngectomy. They provide acceptable toxicity and good palliative effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Although surgical resection constitutes the primary curative option when recurrent disease is resectable, in actuality, only a small fraction of patients are suited for an organ-sparing approach. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] However, there are no well-defined recommendations for selecting patients for interventional radio-oncologic treatment and, in most cases, the decision is made individually. 10 However, it should be underlined that if locoregional disease is left untreated, the prognosis and quality of life are quite poor with sole chemotherapy offering a median survival of 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although surgical resection constitutes the primary curative option when recurrent disease is resectable, in actuality, only a small fraction of patients are suited for an organ-sparing approach. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] However, there are no well-defined recommendations for selecting patients for interventional radio-oncologic treatment and, in most cases, the decision is made individually. 10 However, it should be underlined that if locoregional disease is left untreated, the prognosis and quality of life are quite poor with sole chemotherapy offering a median survival of 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…10 Thinking with the wisdom of hindsight, image-based interstitial brachytherapy has proven to be an effective alternative for this poor-prognosis population by escalating the biologically effective dose (BED) to the treatment target while ameliorating conformity. 8,[15][16][17][18][19][20][21][22][23][24][25][26][27][28] The purpose of the present work was to present 4 challenging cases with locally progressive disease of rare histopathological entities in which salvage surgery after previous EBRT in the head and neck was not possible. A number of publications have reported good local control associated with acceptable complication rates in the treatment of recurrent head and neck cancer with afterloaded brachytherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35][36][37][38][39][40][41][42][43][44][45][46] Based on these articles, we added the article by Johansson et al, 47 which was not found in both searches, and the article of Strnad et al, 48 which was published after our search. We excluded four articles of the Erlangen group since these were the previous results from the same studies with shorter follow-up time (Tables 5 and 6).…”
Section: Head and Neck Cancermentioning
confidence: 99%
“…Two studies reported data on primary or recurrent lip carcinoma. 40,47 The other five articles reported on recurrence in HN cancer, whereas Bartochowska et al 34 also did a subanalysis on recurrence in specifically larynx carcinoma.…”
Section: Head and Neck Cancermentioning
confidence: 99%